2004
DOI: 10.1038/sj.ejhg.5201269
|View full text |Cite
|
Sign up to set email alerts
|

CNGB3 mutations account for 50% of all cases with autosomal recessive achromatopsia

Abstract: Achromatopsia is a congenital, autosomal recessively inherited disorder characterized by a lack of color discrimination, low visual acuity (o0.2), photophobia, and nystagmus. Mutations in the genes for CNGA3, CNGB3, and GNAT2 have been associated with this disorder. Here, we analyzed the spectrum and prevalence of CNGB3 gene mutations in a cohort of 341 independent patients with achromatopsia. In 163 patients, CNGB3 mutations could be identified. A total of 105 achromats carried apparent homozygous mutations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
176
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 217 publications
(191 citation statements)
references
References 25 publications
4
176
0
11
Order By: Relevance
“…4 CNGB3 is also mutated in about 50% of human patients with achromatopsia. 17 On the other hand, XLPRA is caused by microdeletions in exon ORF15 of RPGR, and the mutation causing a frameshift has a severe, and aggressive early-onset cone/rod disease phenotype similar to what is found in RPGR/XLRP patients. 6,18 Previous studies have shown that sequences upstream of the human red or long wavelength (L) opsin gene contain a core promoter with a locus control region (LCR) that confers expression in cones of transgenic mice.…”
Section: Introductionmentioning
confidence: 98%
“…4 CNGB3 is also mutated in about 50% of human patients with achromatopsia. 17 On the other hand, XLPRA is caused by microdeletions in exon ORF15 of RPGR, and the mutation causing a frameshift has a severe, and aggressive early-onset cone/rod disease phenotype similar to what is found in RPGR/XLRP patients. 6,18 Previous studies have shown that sequences upstream of the human red or long wavelength (L) opsin gene contain a core promoter with a locus control region (LCR) that confers expression in cones of transgenic mice.…”
Section: Introductionmentioning
confidence: 98%
“…[22][23][24][25][26] Compared with the other two genes known to cause achromatopsia CNGA3 and CNGB3, GNAT2 is only a minor achromatopsia locus, which account for 2% of the cases. 7 As this is the largest sibship affected with GNAT2 achromatopsia, this family gave a unique opportunity for phenotype-genotype analysis and comparison to other complete achromatopsia subtypes. Although some CNGB3 affected subjects and carriers presented a macular atrophy and peripheral granularity, respectively, 27 no macular atrophy was identified in ACH-G patients' and carriers' fundi.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Rod monochromacy is inherited as an autosomal recessive trait with complete penetrance and is associated with mutations in four different genes. Two genes, CNGA3 and CNGB3, which are more frequently associated to achromatopsia, 7 encode the alpha and beta subunits of cyclic guanosine monophosphate-gated cation channel in cone cells, respectively. 8,9 This channel is involved in cone membrane hyperpolarization during visual transduction.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In other populations, CNGA3-associated ACHM seems to be more prevalent. 4,5 CNGA3 and CNGB3 mutations result in a loss of cone photoreceptor function in humans and in animals with mutations in the homologous genes.…”
Section: Introductionmentioning
confidence: 99%